(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nowadays, in the field of pedagogy, the terms pedagogical technology, educational technology, teaching technology are often used. To date, in the pedagogical literature, reports on educational problems, official documents, the concepts of "new pedagogical technology", "advanced pedagogical technology", "modern educational technology" have not yet been standardized, as explained in encyclopedias. q, a single interpretation of its content has not been developed and therefore there are many different definitions of the phrase.